2018
DOI: 10.1007/s00438-018-1451-4
|View full text |Cite
|
Sign up to set email alerts
|

RIT2: responsible and susceptible gene for neurological and psychiatric disorders

Abstract: RIT2 gene was recently introduced as a susceptibility gene in neurological disorders, a group of major problems in human society affecting millions of people worldwide. Several variants, including single nucleotide polymorphisms and CNVs, have been identified and studied in different populations. In this review, we have summarized the studies relevant to the RIT2 gene and its related disorders, including Parkinson's disease, schizophrenia, and autism. The protein product of RIT2 is a member of the Ras superfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Rin is involved in calcium-mediated processes in cells and binds to calmodulin through a C-terminal binding motif, regulating the Rin-mediated pathway (Hoshino and Nakamura, 2002; Daneshmandpour et al, 2018). Rin has an important role in intracellular signaling and interacts with DAT (dopamine active transporter) in lipid raft microdomains (Navaroli et al, 2011).…”
Section: The Ras Family In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rin is involved in calcium-mediated processes in cells and binds to calmodulin through a C-terminal binding motif, regulating the Rin-mediated pathway (Hoshino and Nakamura, 2002; Daneshmandpour et al, 2018). Rin has an important role in intracellular signaling and interacts with DAT (dopamine active transporter) in lipid raft microdomains (Navaroli et al, 2011).…”
Section: The Ras Family In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
“…Recent genome wide association study (GWAS) and meta-analysis results introduced Rit2 as a novel susceptibility locus, in association with decreased Rin expression in the substantia nigra pars compacta (SNc) of PD patients (Bossers et al, 2009; Latourelle et al, 2012; Pankratz et al, 2012). However, the results of RIT2 polymorphisms studies in different populations are controversial, which may be due to genetic context difference and environmental factors (Daneshmandpour et al, 2018). Therefore, further functional study, animal study and larger study with various population samples might give more detailed role of RIT2 in cells and groups in PD pathogenesis.…”
Section: The Ras Family In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuronal, Ras-like GTPase, Rit2 (aka: Rin, ras-like in neurons), is enriched in DANs [8] and is required for NGF-mediated MAP kinase activation in neuroendocrine cells [9,10]. Multiple genome-wide association studies (GWAS) identified Rit2 in several DA-related disorders, including PD [11], ASD [12], essential tremor, schizophrenia, and bipolar disorder [13][14][15]. We previously demonstrated that Rit2 binds directly to the presynaptic, cocaine-sensitive DAT, and that Rit2 activity is required for PKC-stimulated DAT endocytosis in cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Six of the ten genes were previously reported to be associated with a range of psychiatric and neurological disorders. In addition to NRG1 46,47 , this included ZNF804B 48 , CDH12 49 , CLSTN2 50,51 , RIT2 52 , and MCTP1 53 . This pattern is somewhat reminiscent of so-called Von Economo neurons (VENs) that are known to be altered in diseases such as Alzheimer, autism, and schizophrenia 54-56 .…”
Section: Resultsmentioning
confidence: 99%